Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3727/096368911x564976
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Encapsulated Hepatocytes during Acute Liver Failure Improves Survival without Stimulating Native Liver Regeneration

Abstract: The aim of this study was to evaluate the effects of intraperitoneal transplantation of encapsulated human hepatocytes on liver metabolism and regeneration of mice with acute liver failure. Primary human hepatocytes were immortalized using lentiviral vectors coding for antiapoptotic genes and microencapsulated using alginate-polylysine polymers. In vitro, immortalized human hepatocytes showed low, but stable, synthetic and catabolitic functions over time, when compared to primary hepatocytes. In vivo, mice wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 43 publications
2
52
0
Order By: Relevance
“…Micropores permit exchanges of nutrients, oxygen, and small-sized molecules. The promising first transplants with encapsulated hepatocytes in pig-to-rodent animal models showed that such transplanted encapsulated hepatocytes were still functional over several weeks [4][5][6]. In a pig-to-baboon model, 75% of baboons after induction of fulminant liver failure and subsequent transplantation with encapsulated hepatocytes recovered from liver injury [7], demonstrating further the therapeutic potential of such a treatment.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Micropores permit exchanges of nutrients, oxygen, and small-sized molecules. The promising first transplants with encapsulated hepatocytes in pig-to-rodent animal models showed that such transplanted encapsulated hepatocytes were still functional over several weeks [4][5][6]. In a pig-to-baboon model, 75% of baboons after induction of fulminant liver failure and subsequent transplantation with encapsulated hepatocytes recovered from liver injury [7], demonstrating further the therapeutic potential of such a treatment.…”
Section: Introductionmentioning
confidence: 84%
“…Porcine hepatocyte cell transplantation might present an alternative solution to overcome acute liver failure damages by replacing the metabolic function of the liver until its recovery. Earlier studies in mice with acetaminophen-and hepatectomy-induced fulminant liver failure showed that transplantation of microencapsulated human or porcine hepatocytes increased survival rates of mice [5,6] and the first protocols for porcine hepatocyte isolation and encapsulation with Alg-PLL capsules were applied [5,6]. Here, we developed an optimized high-yield porcine hepatocyte isolation protocol from 10-kilogram pigs.…”
Section: Discussionmentioning
confidence: 99%
“…This deficiency may be attributed to the use of synthetic material on which the cells are seeded in the apparatus. Functional efficiency can be improved by providing a more natural substrate in the extracorporeal device to allow cells to function more closely to an in vivo state [131,132]. Natural ECM should enable cells to maintain higher functionality and ultimately lead to greater levels of protein secretion and waste metabolism.…”
Section: Liver Extracellular Matrix (Ecm) Supportmentioning
confidence: 97%
“…In this study cells were microencapsulated in alginate-poly(L-lysine)-alginate microspheres. Porcine hepatocytes microencapsulated in alginatepoly(L-lysine)-alginate microspheres manifested in vitro production of albumin and urea, and degraded ammonium, diazepam and lidocaine; in vivo a 55% increase in survival of mice with fulminant liver failure was shown [29,64]. Recently, porcine hepatocytes microencapsulated in alginate-poly(L-lysine)-alginate microspheres (Fig.…”
Section: Preclinical Studies With Encapsulated Xenogeneic Hepatocytesmentioning
confidence: 99%